Sliding member and sliding member for internal combustion engine
By forming a coating layer composed of precipitation-hardened copper alloy particles on the substrate and combining nickel and silicon elements, the problem of insufficient wear resistance of the hard coating is solved, and the wear resistance of the sliding component is improved.
Patent Information
- Application Number
- CN202310054572.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-02-03
- Filing Date
- 2018-02-02
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2038-02-02
AI Technical Summary
The hard coatings in the prior art have insufficient wear resistance.
A coating layer is formed on a substrate. The coating layer is composed of precipitation-hardened copper alloy particles. The copper alloy parts are bonded via interfaces and contain nickel and silicon as additive elements to form a uniform nickel silicide precipitation phase.
The wear resistance of the sliding component is improved and the wear resistance of the sliding component is enhanced.
Smart Images

Figure CN116180069B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with the application date of February 2, 2018, application number 201880009616.1, and invention name “Sliding component and sliding component for internal combustion engine”. Technical Field
[0002] The present invention relates to a sliding member and a sliding member for an internal combustion engine. Background Art
[0003] Patent Document 1 discloses a method for forming a hard coating that can form a hard coating on the surface of a substrate through cold strain-induced transformation. This method is a method for forming a hard metal coating by blowing solid metal powder onto the surface of a substrate using a compressed gas as a medium. In this formation method, the metal powder is made of a metal material that can cause strain-induced transformation, and is sprayed onto the substrate at such a high speed that it causes strain-induced transformation, so that the metal powder is plastically deformed into a flat shape and deposited as a layer on the surface of the substrate, while also causing strain-induced transformation of the previously deposited metal powder. In this way, the formation method is characterized in that the method forms a metal coating on the surface of the substrate, wherein the coating is harder than the metal powder before being sprayed onto the substrate.
[0004] [Prior Art]
[0005] [Patent Document]
[0006] Patent Document 1: JP 5202024B Summary of the Invention
[0007] Problems to be solved by the invention
[0008] However, the hard coating in Patent Document 1 has a problem in that its wear resistance is insufficient.
[0009] The present invention has been made in view of the above-mentioned problems in the prior art. An object of the present invention is to provide a sliding member having excellent wear resistance, and a sliding member for an internal combustion engine.
[0010] Solutions for solving problems
[0011] The present inventors have conducted intensive research to achieve the above-mentioned objectives. As a result, the present inventors have discovered that the above-mentioned objectives can be achieved by forming a coating layer comprising predetermined copper alloy portions derived from precipitation-hardened copper alloy particles, wherein the copper alloy portions are bonded to each other via interfaces between the copper alloy portions. This has led to the completion of the present invention.
[0012] Effects of the Invention
[0013] According to the present invention, a sliding member having excellent wear resistance and a sliding member for an internal combustion engine can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a schematic cross-sectional view of a sliding member according to a first embodiment of the present invention.
[0015] Figure 2 for the reason Figure 1 : is an enlarged view of a portion of the sliding member surrounded by line II shown in .
[0016] Figure 3 for the reason Figure 1 : is an enlarged view of a portion of the sliding member surrounded by line III shown in .
[0017] Figure 4 is a schematic cross-sectional view of a sliding member according to a second embodiment of the present invention.
[0018] Figure 5 for the reason Figure 4 : is an enlarged view of a portion of the sliding member surrounded by line V shown in .
[0019] Figure 6 for the reason Figure 4 : is an enlarged view of the portion surrounded by line VI of the sliding member shown in .
[0020] Figure 7 is a schematic cross-sectional view of a sliding member according to a third embodiment of the present invention.
[0021] Figure 8 for the reason Figure 7 : is an enlarged view of a portion of the sliding member surrounded by line VIII shown in .
[0022] Figure 9 for the reason Figure 7 1 is an enlarged view of a portion of the sliding member surrounded by line IX shown in .
[0023] Figure 10 is a schematic cross-sectional view of a sliding member according to a fourth embodiment of the present invention.
[0024] Figure 11 Schematic cross-sectional view of a sliding member for an internal combustion engine including the sliding member at a sliding portion of the internal combustion engine.
[0025] Figure 12 This is a schematic cross-sectional view of a bearing mechanism for an internal combustion engine having a sliding member in a bearing metal of the bearing mechanism of the internal combustion engine.
[0026] Figure 13 This is a cross-sectional view showing the outline of the wear testing device.
[0027] Figure 14 This is a transmission electron microscope (TEM) cross-sectional image of the sliding member of Example 3.
[0028] Figure 15 Graphs showing the results of energy dispersive X-ray (EDX) analysis of the sliding member of Example 3. DETAILED DESCRIPTION
[0029] The sliding member according to the embodiment of the present invention and the sliding member for an internal combustion engine are described in detail below. The phrase "at least one of A, B, and C" means "(A), (B), (C), (A and B), (A and C), (B and C), or (A, B, and C)".
[0030] First embodiment
[0031] First, referring to the accompanying drawings, a sliding member according to a first embodiment of the present invention will be described in detail. For descriptive purposes, the sizes of the drawings mentioned in the following embodiments are exaggerated and may be different from the actual sizes.
[0032] Figure 1 is a schematic cross-sectional view of a sliding member according to a first embodiment of the present invention. Figure 2 for the reason Figure 1 An enlarged view of the portion of the sliding member surrounded by line II. Figure 3 for the reason Figure 1 An enlarged view of the portion of the sliding member surrounded by line III. Figure 1 and 2 As shown, the sliding member 1 of this embodiment includes a substrate 10 and a coating layer 20 formed on the substrate 10. The coating layer 20 includes copper alloy portions 21 derived from precipitation-hardened copper alloy particles. Furthermore, in the coating layer 20, the copper alloy portions 21, 21 are bonded to each other via interfaces 21a between the copper alloy portions. Furthermore, although not shown, the copper alloy portions contain nickel and silicon as additive elements. The copper alloy portions contain 2 to 5% by mass of nickel. The coating layer 20 may have pores 20a.
[0033] In addition, if Figure 3 As shown in , the sliding member 1 of this embodiment preferably has at least one copper alloy portion 21 containing at least one precipitated phase 25 inside the copper alloy portion and at an interface 21a between the copper alloy portions 21, 21. The coating layer 20 may have pores 20a.
[0034] In the present invention, "precipitation hardening type copper alloy" refers not only to a copper alloy that has been precipitation hardened, but also to a copper alloy before precipitation hardening. In the copper alloy portion, it is preferred that all copper alloy portions are copper alloys that have been precipitation hardened, but it is not limited thereto. For example, among a plurality of copper alloy portions, a portion of the copper alloy portions may be a copper alloy that has been precipitation hardened, and the remaining copper alloy portions may be a copper alloy before precipitation hardening. In addition, for example, all copper alloy portions may be made of a copper alloy before precipitation hardening. Precipitation hardening type copper alloys are also referred to as particle dispersion strengthening type copper alloys.
[0035] As described above, the sliding member of this embodiment includes a substrate and a coating layer formed on the substrate. The coating layer includes copper alloy portions derived from precipitation-hardened copper alloy particles, the copper alloy portions are bonded to each other via interfaces between the copper alloy portions, the copper alloy portions contain nickel and silicon as additive elements, and the copper alloy portions contain 2 to 5% by mass of nickel. Consequently, the sliding member exhibits excellent wear resistance.
[0036] Furthermore, as described above, in the sliding member of the present embodiment, at least one copper alloy portion preferably contains at least one precipitated phase inside the copper alloy portion and at the interface between the copper alloy portions. Such a sliding member has further excellent wear resistance.
[0037] It is currently presumed that the above-described effects are obtained based on at least one of the following reasons.
[0038] In a copper alloy portion comprising nickel and silicon, when the nickel content is 2 to 5% by mass, it is believed that the precipitation of compounds comprising nickel, silicon, etc. will prevent the copper alloy portion from being easily deformed, thereby improving their wear resistance. It is also believed that this is the result of a precipitated phase being uniformly contained in the coating layer, wherein the precipitated phase is made of nickel silicide (Ni2Si) having a significant effect in improving wear resistance. When the nickel content is less than 2% by mass, the amount of precipitated phase formed in the coating layer and made of nickel silicide (Ni2Si) having an improvement effect in wear resistance is insufficient. In addition, when the nickel content exceeds 5% by mass, a precipitated phase made of nickel silicide (Ni2Si) having an excellent improvement effect in wear resistance is unevenly formed in the coating layer. Although not particularly limited, the ratio of nickel content to silicon content (Ni:Si) is preferably in the range of 3.5:1 to 4.5:1 in terms of mass ratio. In addition, the silicon content is preferably in the range of 0.5 to 1.25% by mass. However, needless to say, the above-mentioned contents and ratios are not limited to these ranges and may be outside these ranges as long as the effects of the present invention can be exhibited.
[0039] This effect is believed to be achieved, for example, due to the following reason: when precipitation-hardening copper alloy particles (hereinafter, also referred to as "copper alloy particles"), which are used as a material for the sliding member manufacturing method, are blown onto the substrate and collide with the substrate and the copper alloy portion attached to the substrate, their kinetic energy is partially converted into thermal energy. This conversion promotes the deposition and atomic diffusion between the substrate and the copper alloy particles, and between the copper alloy particles and the copper alloy portion, resulting in the uniform formation of the precipitated phase. This will be described in detail later.
[0040] However, it is needless to say that the scope of the present invention will include other cases in which the above-mentioned effects are obtained based on reasons other than the above-mentioned reasons.
[0041] In the present invention, "copper alloy parts are bonded to each other via the interface between the copper alloy parts" means that at least one of welding, atomic diffusion, and biting (penetration) and formation of plastic deformation parts (described in detail later) occurs between the copper alloy parts. In the first or second embodiment, biting (penetration) or formation of plastic deformation parts may occur.
[0042] The components are described in more detail below.
[0043] The substrate 10 is not particularly limited. However, it is preferably a metal suitable for the method of manufacturing the sliding member, that is, the method of forming the coating layer, which will be described in detail later. Furthermore, when the sliding member is used as a sliding member for an internal combustion engine, it goes without saying that the substrate is preferably a substrate that can be used in the high-temperature environment in which the sliding member will be used.
[0044] Examples of preferably used metals include alloys of aluminum, iron, titanium, copper, and the like, which are well known in the art.
[0045] Examples of preferably used aluminum alloys include AC2A, AC8A, and ADC12 specified in the Japanese Industrial Standards. Examples of preferably used iron alloys include SUS304 specified in the Japanese Industrial Standards and iron-based sintered alloys. Examples of preferably used copper alloys include beryllium copper and copper-based sintered alloys.
[0046] The porosity of the coating layer 20 is not particularly limited. However, insofar as a high porosity in the coating layer can lead to insufficient strength and low wear resistance, the porosity of the coating layer is preferably as low as possible. In addition, in order to obtain a sliding component with high thermal conductivity, the porosity of the coating layer in its cross section is preferably less than 3 area%, more preferably less than 1 area%, and particularly preferably 0 area%. Since the porosity can be reduced to 0.1 area%, it is preferred to have a porosity in the range of 0.1 area% to 3 area% in terms of obtaining excellent wear resistance and improvement in productivity with a good balance. However, needless to say, the porosity is not limited to these ranges and can be outside these ranges as long as the effect of the present invention can be shown. The porosity of the coating layer in its cross section can be calculated by, for example, observing a scanning electron microscope (SEM) image of the cross section of the coating layer and image processing such as binarization of the scanning electron microscope (SEM) image.
[0047] In addition, the thickness of the coating layer 20 is not particularly limited. That is, the thickness of the coating layer can be appropriately adjusted according to the temperature and sliding environment of the area where the coating layer is applied. For example, the thickness range is preferably 0.05 mm to 5.0 mm, and more preferably 0.1 mm to 2.0 mm. When the thickness of the coating layer is less than 0.05 mm, the rigidity of the coating layer itself becomes insufficient, which may lead to plastic deformation, especially when the strength of the substrate is low. When the thickness of the coating layer is greater than 10 mm, the coating layer may peel off due to the relationship between the residual stress generated during film formation and the interface adhesion force.
[0048] The precipitation-hardening copper alloy contained in the copper alloy portion 21 is not particularly limited as long as it contains nickel and silicon and the nickel content ranges from 2 to 5 mass %. A so-called Corson alloy is preferably used. This imparts excellent wear resistance.
[0049] However, precipitation-hardening copper alloys are not limited to those described above. For example, precipitation-hardening copper alloys to which chromium, zirconium, or vanadium are further added, either individually or in any combination, can be used. This allows for the use of various materials depending on the specifications required for the sliding member. Needless to say, other elements can be further added to the precipitation-hardening copper alloys described above.
[0050] Second embodiment
[0051] Next, referring to the accompanying drawings, a sliding member according to a second embodiment of the present invention will be described in detail. Components identical to those described in the previous embodiment will be given the same reference numerals, and description thereof will be omitted.
[0052] Figure 4 is a schematic cross-sectional view of a sliding member according to a second embodiment of the present invention. Figure 5 for the reason Figure 4: is an enlarged view of a portion of the sliding member surrounded by line V shown in . Figure 6 for the reason Figure 4 An enlarged view of the portion of the sliding member surrounded by line VI shown in FIG. Figures 4 to 6 As shown in , the sliding member 2 of the present embodiment is different from the sliding member of the above-mentioned first embodiment in that the coating layer 20 includes a hard particle portion 23 which is harder than the copper alloy portion 21 and is derived from hard particles, and, for example, the copper alloy portions 21, 21, the copper alloy portion 21 and the hard particle portion 23, and the hard particle portions 23, 23 are bonded to each other via interfaces therebetween.
[0053] In addition, if Figure 5 As shown in , in the sliding member 2 of the present embodiment, at least one copper alloy part 21 preferably contains at least one precipitated phase 25 inside the copper alloy part 21 and at an interface 21a between the copper alloy parts 21, 21. The coating layer 20 may have pores 20a.
[0054] In addition, if Figure 6 As shown in FIG, in the sliding member 2 of this embodiment, the hard particle portion 23 is harder than the copper alloy portion 21. This facilitates the precipitation of the precipitated phase 25 near the interface 21a of the copper alloy portion 21 adjacent to the hard particle portion 23 (in this specification, "near the interface of the copper alloy portion" means, for example, the region of the copper alloy portion 21 from the interface 21a to about 1 μm inward, as indicated by arrow X in the figure). The precipitated phase 25 containing nickel silicide (Ni2Si) can be easily and uniformly contained. The coating layer 20 may have pores 20a.
[0055] As described above, the sliding member of this embodiment includes a substrate and a coating layer formed on the substrate, wherein the coating layer includes the predetermined copper alloy portion and a hard particle portion that is harder than the copper alloy portion, and these portions (e.g., the copper alloy portions themselves, the copper alloy portion and the hard particle portion, and the hard particle portions themselves) are bonded to each other via interfaces therebetween. Consequently, the sliding member exhibits further excellent wear resistance.
[0056] It is currently presumed that the above-described effects are obtained based on at least one of the following reasons.
[0057] This effect is believed to be achieved, for example, due to the following reason: when a mixture containing copper alloy particles, which are used as a material for the manufacturing method of a sliding member, and hard particles harder than the copper alloy particles, is blown onto a substrate and the hard particles collide with the substrate, if, for example, the substrate has an oxide film on its surface that inhibits adhesion between the substrate and the coating layer, the oxide film is removed, exposing and forming a new interface with the substrate that exhibits excellent adhesion with the coating layer. This will be described in detail later.
[0058] It is also considered that this effect is obtained, for example, due to the following reason: when copper alloy particles and hard particles are blown onto the substrate and the hard particles collide with the copper alloy portion attached to the substrate, the kinetic energy is partially converted into thermal energy, which promotes welding and atomic diffusion in the copper alloy portion, thereby uniformly forming a precipitated phase.
[0059] It is considered that the copper alloy portions 21 , 21 , and the copper alloy portion 21 and the hard particle portion 23 are relatively more easily bonded than the hard particle portions 23 , 23 .
[0060] However, it is needless to say that the scope of the present invention includes the case where the above-mentioned effects are obtained based on reasons other than the above-mentioned reasons.
[0061] The hard particle portion 23 will be described in more detail. The hard particle portion is not particularly limited as long as it is harder than the copper alloy portion. For example, an alloy particle portion or a hard particle portion obtained by mixing these particles in any proportion may be used. Furthermore, although not particularly limited, the hard particle portion is preferably harder than the base material. Furthermore, for example, in order to obtain an alloy particle portion having further excellent wear resistance, it is preferred to use iron-based alloy particles, cobalt-based alloy particles, chromium-based alloy particles, nickel-based alloy particles, or molybdenum-based alloy particles, or hard particles obtained by mixing these particles in any proportion.
[0062] For example, the Vickers hardness measured and calculated according to the Vickers hardness test defined in the Japanese Industrial Standard (JIS Z 2244) can be used as an indicator of the hardness of the copper alloy portion and the hard particle portion, and further, the copper alloy particles and hard particles described in detail later. In addition, the arithmetic mean obtained by measuring about three to thirty particles, at least three to five particles, for the particles, and about three to thirty positions, at least three to five positions for the copper alloy portion and the hard particle portion in the coating layer is used as the Vickers hardness. In addition, when measuring and calculating the Vickers hardness of the copper alloy portion and the hard particle portion, if necessary, observation of a scanning electron microscope (SEM) image and a transmission electron microscope (TEM) image, and energy dispersive X-ray (EDX) spectroscopy analysis can be combined.
[0063] Examples of the above-mentioned iron-based alloys include SUS 440C specified in the Japanese Industrial Standards. Examples of cobalt-based alloys include TRIBALOY (registered trademark) T-400 and T-800. Examples of chromium-based alloys include chromium-iron alloys. Examples of nickel-based alloys include TRIBALOY (registered trademark) T-700. Examples of molybdenum-based alloys include molybdenum-iron alloys. Examples of ceramics include WC / Co and Al2O3. Among them, cobalt-based alloys with excellent wear resistance are preferably used. Specifically, cobalt-based alloys such as TRIBALOY (registered trademark) T-400 and T-800 are preferably used.
[0064] Although not particularly limited, in terms of improving wear resistance and thermal conductivity depending on the needs, the ratio of the hard particle portion in the cross section of the coating layer is preferably in the range of 1 area % to 50 area %, more preferably 1 area % to 25 area %, still more preferably 1 area % to 18 area %, and particularly preferably 5 area % to 18 area %. However, needless to say, the ratio is not limited to these ranges and may be outside these ranges as long as the effects of the present invention can be shown. The ratio of the hard particle portion in the cross section of the coating layer can be calculated by observing a scanning electron microscope (SEM) image of the cross section of the coating layer and image processing of the scanning electron microscope (SEM) image such as binarization. In addition, needless to say, the area % calculated by observation of the cross section can be regarded as volume %, and the volume % can be converted into weight % using the density of the particles.
[0065] As described above, in terms of improving wear resistance and thermal conductivity, the ratio of the hard particle portion in the cross section of the coating layer is preferably in the range of 1 area % to 50 area %. However, for applications that do not generally require high thermal conductivity but do require excellent wear resistance, the ratio of the hard particle portion in the cross section of the coating layer is in the range of 50 area % to 99 area %. Furthermore, this may include portions other than the copper alloy portion and the hard particle portion.
[0066] The hard particle portion 23 is not particularly limited as long as it is harder than the copper alloy portion. However, it is preferably non-spherical in terms of increasing the contact area with the copper alloy portion and improving wear resistance.
[0067] "The hard particle portion has a non-spherical shape" means in this article that the aspect ratio of the hard particle portion is not less than 1.3 in terms of its median value. Although not particularly limited, more specifically, the aspect ratio of the hard particle portion is preferably in the range of 1.3 to 2.0 in terms of its median value. When observing any cross-section along the layer thickness direction of the coating layer with a scanning electron microscope (SEM), the "aspect ratio" is defined as (maximum long diameter / width orthogonal to the maximum long diameter) in each hard particle portion. In addition, the "maximum long diameter" refers to the maximum distance between any two points on the outline of the hard particle portion when observing any cross-section along the layer thickness direction of the coating layer with a scanning electron microscope (SEM). When calculating the median value of the aspect ratio, it is necessary to measure, for example, about three to thirty, at least about three to five hard particle portions observed in several to dozens of fields of view.
[0068] Third embodiment
[0069] Next, a sliding member according to a third embodiment of the present invention will be described in detail with reference to the accompanying drawings. Components identical to those described in the previous embodiments will be given the same reference numerals, and descriptions thereof will be omitted.
[0070] Figure 7 is a schematic cross-sectional view of a sliding member according to a third embodiment of the present invention. Figure 8 for the reason Figure 7 : is an enlarged view of a portion of the sliding member surrounded by line VIII shown in . Figure 9 for the reason Figure 7 An enlarged view of the portion of the sliding member surrounded by line IX shown in FIG. Figures 7 to 9 As shown in FIG, the sliding member 3 of the present embodiment differs from the sliding member of the first or second embodiment described above in that the base material 10 has a plastically deformed portion 10 b made of a flat concave portion, and the coating layer 20 includes a plastically deformed portion 20 b having a structure in which a copper alloy portion 21 having a flat shape is accumulated. Although not shown, it is needless to say that the scope of the present invention includes a case in which the coating layer is formed only of the copper alloy portion and the hard particle portion, as well as a case in which one of the base material and the coating layer has a plastically deformed portion.
[0071] As described above, the sliding member of this embodiment includes a substrate and a coating layer formed on the substrate. The coating layer includes the predetermined copper alloy portion described above and, if necessary, further includes a hard particle portion that is harder than the copper alloy portion. These portions (e.g., the copper alloy portions themselves, the copper alloy portions and the hard particle portion, and the hard particle portions themselves) are bonded to each other via interfaces therebetween. Furthermore, at least one of the substrate and the coating layer includes at least one plastically deformed portion. Consequently, the sliding member exhibits further excellent wear resistance.
[0072] It is currently presumed that the above-described effects are obtained based on at least one of the following reasons.
[0073] This effect is believed to be achieved by blowing a mixture containing copper alloy particles and hard particles harder than the copper alloy particles, which is a material used in the sliding member manufacturing method, onto a substrate and causing the hard particles to collide with the substrate. If the substrate has an oxide film on its surface that inhibits adhesion between the substrate and the coating layer, the oxide film is removed, exposing and forming a new interface with the substrate that exhibits excellent adhesion with the coating layer. This will be described in detail later.
[0074] It is also believed that this effect is achieved due to the following reasons: for example, when the copper alloy particles collide with the substrate and the copper alloy part attached to the substrate, the kinetic energy is partially converted into thermal energy, which promotes welding and atomic diffusion between the substrate and the copper alloy particles, or between the copper alloy particles and the copper alloy part.
[0075] It is further believed that this effect is achieved by an anchoring effect caused by the copper alloy particles sinking into the substrate when they collide with the substrate, thereby improving the adhesion between the substrate and the coating layer. In other words, as described above, it is believed that this effect is achieved by the formation of a plastically deformed portion comprising a flat recessed portion on the substrate, which improves the adhesion between the substrate and the coating layer.
[0076] Furthermore, it is believed that this effect is obtained by improving the adhesion between the copper alloy parts in the coating layer due to the copper alloy particles and the copper alloy parts becoming flat when the copper alloy particles collide with the substrate and the copper alloy parts attached to the substrate. That is, as described above, it is also believed that this effect is obtained by reducing the gaps (pores) between the copper alloy parts due to the formation of a plastic deformation part having a structure in which the copper alloy parts having a flat shape are accumulated on the coating layer, which improves the adhesion between the copper alloy parts in the coating layer. For example, in Figure 5 In the embodiment, the coating layer 20 may have pores 20a. On the other hand, in Figure 8 In the embodiment, the pores in the coating layer 20 are reduced and are hardly observed.
[0077] Furthermore, it is also considered that this effect is achieved by the following process: when the copper alloy particles collide with the substrate or the copper alloy part attached to the substrate, a flat recessed portion is formed on the substrate, or when the copper alloy particles and the copper alloy part are flattened, in other words, when a plastically deformed portion is formed on the substrate or the coating layer, a process of welding and atomic diffusion between the substrate and the copper alloy particles or between the copper alloy particles and the copper alloy part due to heat caused by plastic deformation.
[0078] It is further believed that this effect is achieved by the anchoring effect caused by the hard particles sinking into the substrate or the copper alloy portion attached to the substrate when they collide with the substrate, thereby improving the adhesion between the substrate and the coating layer. In other words, as described above, it is believed that this effect is achieved by the formation of a plastically deformed portion comprising a flat concave portion on the substrate, which improves the adhesion between the substrate and the coating layer.
[0079] It is further believed that this effect is achieved due to the following reason: when the copper alloy particles and hard particles are blown onto the substrate, the hard particles are sunk into the copper alloy portion attached to the substrate, or the copper alloy particles are sunk into the hard particle portion attached to the substrate, resulting in an anchoring effect that improves the adhesion between the copper alloy portion and the hard particles in the coating layer. When the hard particle portion has the above-mentioned non-spherical shape, the hard particles are easily sunk into the copper alloy portion attached to the substrate, and the copper alloy particles are easily sunk into the hard particle portion attached to the substrate.
[0080] However, it is needless to say that the scope of the present invention includes the case where the above-mentioned effects are obtained by causes other than the above-mentioned causes.
[0081] Fourth Implementation Plan
[0082] Next, a sliding member according to a fourth embodiment of the present invention will be described in detail with reference to the accompanying drawings. Components identical to those described in the previous embodiments will be given the same reference numerals, and descriptions thereof will be omitted.
[0083] Figure 10 : is a schematic cross-sectional view of a sliding member according to a fourth embodiment of the present invention. Figure 10 As shown in , the sliding member 4 of the present embodiment is different from the sliding members of the first to third embodiments in that the sliding member 4 includes a predetermined intermediate layer 30 formed over the entire gap between the substrate 10 and the coating layer 20. The predetermined intermediate layer 30 includes a diffusion layer or an intermetallic compound layer, or a diffusion layer and an intermetallic compound layer. In the case where the intermediate layer includes a diffusion layer, the intermediate layer may be a diffusion layer. In the case where the intermediate layer includes an intermetallic compound layer, the intermediate layer may be an intermetallic compound layer. Although not shown, it is needless to say that the scope of the present invention includes a case where the coating layer has only a copper alloy portion and a copper alloy portion in the hard particle portion, a case where both the substrate and the coating layer have a plastic deformation portion, and a case where one of the substrate and the coating layer has a plastic deformation portion.
[0084] As described above, the sliding member of this embodiment includes a substrate and a coating layer formed on the substrate. The coating layer includes the predetermined copper alloy portion described above and, if necessary, a hard particle portion that is harder than the copper alloy portion. These portions (e.g., the copper alloy portions, the copper alloy portion and the hard particle portion, and the hard particle portions) are bonded to each other via interfaces therebetween. Furthermore, the coating layer includes an intermediate layer comprising at least one of a diffusion layer and an intermetallic compound layer, formed at least in a portion of the gap between the substrate and the coating layer. Consequently, this imparts further excellent wear resistance. Needless to say, at least one of the substrate and the coating layer may include a plastically deformable portion.
[0085] It is currently presumed that the above-mentioned effects are obtained based on the following reasons.
[0086] This effect is believed to be achieved, for example, due to the following reasons: when copper alloy particles, which are the material used in the sliding member manufacturing method, are blown onto the substrate and, for example, collide with the substrate, kinetic energy is partially converted into thermal energy; and diffusion of component elements contained in at least one of the substrate and the copper alloy particles and the copper alloy portion attached to the substrate occurs between them, forming an intermediate layer containing at least one of a diffusion layer and an intermetallic compound layer between the substrate and the coating layer. This will be described in detail later.
[0087] In addition, it is considered that this effect is obtained, for example, due to the following reason: when the mixture further containing hard particles is blown onto the substrate and the hard particles collide with the substrate, if, for example, the substrate has an oxide film on its surface that inhibits the adhesion between the substrate and the coating layer, the oxide film is removed to expose and form a new interface with the substrate, thereby promoting the diffusion of the component elements.
[0088] However, it is needless to say that the scope of the present invention includes the case where the above-mentioned effects are obtained based on reasons other than the above-mentioned reasons.
[0089] The intermediate layer 30 will be described in more detail. The intermediate layer includes a diffusion layer or an intermetallic compound layer, or includes a diffusion layer and an intermetallic compound layer. Suitable examples of the diffusion layer include those whose composition has a gradient structure. However, the diffusion layer is not limited to those whose composition has a gradient structure. In addition, although not particularly limited, suitable examples of the intermediate layer including the intermetallic compound layer include a layer having a structure in which the intermetallic compound layer is between the diffusion layers whose composition has a gradient structure. For example, the intermediate layer includes the component elements contained in the substrate and the component elements contained in the copper alloy portion. Specifically, when an aluminum alloy is used as the substrate, an intermediate layer including an alloy including aluminum and copper is formed. However, the intermediate layer is not limited thereto. For example, when stainless steel (SUS) is used for the substrate, an intermediate layer including an alloy including the component elements of stainless steel (SUS) and copper is formed.
[0090] Fifth Implementation Plan
[0091] Next, a sliding member for an internal combustion engine according to a fifth embodiment of the present invention will be described with reference to the accompanying drawings. Specifically, the sliding member includes the above-described sliding member in a sliding portion of the internal combustion engine. Needless to say, the surface side of the coating layer serves as the sliding surface. Components identical to those described in the previous embodiments will be given the same reference numerals, and their description will be omitted.
[0092] Figure 11 Schematic cross-sectional view of a sliding member for an internal combustion engine including a sliding member at a sliding portion of the internal combustion engine. More specifically, Figure 11 Schematic cross-sectional view of a valve actuation mechanism including an engine valve. Figure 11As shown, as cam lobe 40 rotates, valve lifter 41 is pushed downward, compressing valve spring 42. Simultaneously, engine valve 43 is pushed downward, guided by valve guide 45 with valve stem seal 44. As a result, engine valve 43 separates from its seat 46A in cylinder head 46, allowing exhaust port 47 to communicate with the combustion chamber (not shown) (engine valve open state). Further rotation of cam lobe 40 then causes the repulsive force of valve spring 42 to push valve lifter 41, retainer 48, and retaining pin 49 upward, along with engine valve 43. As a result, engine valve 43 contacts seat 46A, isolating exhaust port 47 from the combustion chamber (not shown) (engine valve closed state). In this manner, engine valve 43 opens and closes synchronously with the rotation of cam lobe 40. In this manner, valve stem 43A of engine valve 43 is mounted, lubricated with oil, by press-fitting into valve guide 45 on the cylinder head 46 side. The valve face 43B of the engine valve 43 serving as an on-off valve for the combustion chamber (not shown) is in contact with or out of contact with the seat portion 46A of the engine valve 43 for the cylinder head 46 during operation. Figure 11 The exhaust port 47 side is shown, but the sliding member of the present invention can also be applied to the intake port side (not shown).
[0093] Sliding components with the above-described coating layer, such as the sliding components (1, 2, 3, and 4) according to the first to fourth embodiments, are applied to the sliding surface 46a of the seat 46A of the cylinder head and the engine valve used therein, where the sliding surface 46a is the sliding portion of the engine valve. This imparts excellent wear resistance. Furthermore, by applying the sliding component of the present invention to the cylinder head, a press-fit valve plate can be omitted. As a result, the shapes of the exhaust and intake ports can be flexibly designed, and the diameter of the engine valve can be increased, which can improve engine fuel consumption, power output, and torque.
[0094] Although not shown in the figures, the sliding member having the above-described coating layer, for example, the sliding member according to the first to fourth embodiments, can also be applied to, for example, one or both of the sliding surface of the valve stem and the sliding surface of the mating valve guide, and / or at least one position selected from the group consisting of the sliding surface of the valve stem end, the sliding surface of the valve face, and the sliding surface of the press-fit valve seat. This imparts excellent wear resistance.
[0095] That is, the cylinder head of this embodiment preferably includes the sliding member of the above-described embodiment in the seat portion of the engine valve. Another cylinder head of this embodiment is a cylinder head including a valve seat having the sliding member of the above-described embodiment, and preferably, it has a sliding member in the seat portion of the engine valve of the valve seat. Furthermore, the valve seat of this embodiment preferably includes the sliding member of the above-described embodiment in the seat portion of the engine valve. Furthermore, the engine valve of this embodiment preferably includes the sliding member of the above-described embodiment in the valve face. Furthermore, another engine valve of this embodiment preferably includes the sliding member of the above-described embodiment in the sliding portion that abuts against the valve guide.
[0096] Sixth Implementation Plan
[0097] Next, a sliding member according to a sixth embodiment of the present invention will be described in detail with reference to the accompanying drawings. It goes without saying that the surface side of the coating layer serves as a sliding surface. Components identical to those described in the previous embodiments will be given the same reference numerals, and their description will be omitted.
[0098] Figure 12 Schematic cross-sectional view of a bearing mechanism of an internal combustion engine including a sliding member in a bearing metal of the bearing mechanism of the internal combustion engine. More specifically, Figure 12 Schematic cross-sectional view of a bearing metal used as a sliding member of a connecting rod. Figure 12 As shown, the large end portion 60A of the connecting rod 60 located on the crank side (not shown) is divided into two parts, upper and lower. A bearing metal 62 divided into two parts for supporting the crank pin 61 is provided on the large end portion 60A.
[0099] The sliding member having the coating layer described above, for example, the sliding members (1, 2, 3, 4) according to the first to fourth embodiments described above, is applied to the sliding surface 62a as the bearing metal 62. This imparts excellent wear resistance.
[0100] Although not shown in the figures, the sliding member having the coating layer described above, for example, the sliding member according to the first to fourth embodiments described above, can also be applied to the sliding surface of a bifurcated bearing metal for supporting a piston pin of a connecting rod at the small end portion on the piston side (not shown). This imparts excellent wear resistance.
[0101] That is, the bearing mechanism of the internal combustion engine of this embodiment preferably includes the sliding member of the above-described embodiment in the bearing metal of the bearing mechanism of the internal combustion engine. Alternatively, a film may be formed directly on the sliding surface of the large end side of the connecting rod (directly formed without using metal). Alternatively, a film may be formed directly on the sliding surface of the small end side of the connecting rod (directly formed without using metal).
[0102] The sliding member for an internal combustion engine of the present embodiment can also be applied to piston rings and pistons. That is, it is preferable to apply a coating layer on the surface of the piston ring. In addition, it is preferable to apply a coating layer on the inner surface of the ring groove of the piston. In addition, in the sliding member for an internal combustion engine of the present embodiment, it is preferable to apply a coating layer on the inner surface of the cylinder hole (this can be used as a substitute for a cylinder liner, or as an alternative to hole thermal spraying). In addition, in the sliding member for an internal combustion engine of the present embodiment, it is preferable to apply a coating layer on the metal of the crankshaft journal. In addition, in the sliding member for an internal combustion engine of the present embodiment, it is preferable to form a coating layer directly on the metal part of the crankshaft journal (the coating layer is directly formed without using metal). In addition, in the sliding member for an internal combustion engine of the present embodiment, it is preferable to apply a coating layer on the surface of the metal of the camshaft journal. In addition, in the sliding member for an internal combustion engine of the present embodiment, it is preferable to form a coating layer directly on the metal part of the camshaft journal (the coating layer is directly formed without using metal). Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the cam lobe surface of the camshaft. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the metal of the piston and the piston pin. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to form a coating layer directly on the metal portion of the piston and the piston pin. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the surface of the piston skirt. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the crown surface of the valve lifter. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the side surface of the valve lifter. Furthermore, in the sliding member for an internal combustion engine of the present embodiment, it is preferred to apply a coating layer on the sliding surface of the valve lifter that abuts the lifter hole in the cylinder head. Furthermore, in the sliding member for an internal combustion engine of this embodiment, it is preferable to apply a coating layer to the surface of the sprocket teeth (in this case, for example, the coating layer is formed on a sprocket made of an aluminum sintered alloy, rather than on a sprocket made of an iron sintered alloy). Furthermore, in the sliding member for an internal combustion engine of this embodiment, it is preferable to apply a coating layer to the pins of the chain. Furthermore, in the sliding member for an internal combustion engine of this embodiment, it is preferable to apply a coating layer to the link plates.
[0103] Furthermore, in the sliding members of the first to fourth embodiments described above, a coating layer is preferably applied to the surfaces of the teeth of gears other than internal combustion engine gears (in this case, for example, aluminum alloy gears are used instead of steel gears, and the coating layer is formed on the aluminum alloy). Examples of gears other than internal combustion engine gears include differential gears for automobiles, generators for automobiles, and generators other than generators for automobiles. Furthermore, the sliding members of the first to fourth embodiments described above are preferably applied to general sliding bearings (meaning sliding bearings in the broad sense that are not rolling bearings).
[0104] Next, a method for manufacturing a sliding member is described in detail. The method for manufacturing a sliding member is, for example, a method for manufacturing a sliding member comprising a substrate according to the first to fourth embodiments described above, and a coating layer formed on the substrate, wherein the coating layer comprises the predetermined copper alloy portion, or the predetermined copper alloy portion and the hard particle portion, and these portions (e.g., between the copper alloy portions, between the copper alloy portion and the hard particle portion, and between the hard particle portions) are bonded to each other via the interface therebetween. The method for manufacturing a sliding member comprises the steps of forming a coating layer on the substrate by blowing the predetermined copper alloy particles or a mixture containing the predetermined copper alloy particles and the hard particles onto the substrate in a non-molten state, wherein the coating layer comprises the predetermined copper alloy portion, or the predetermined copper alloy portion and the hard particle portion, and these portions (e.g., between the copper alloy portions, between the copper alloy portion and the hard particle portion, and between the hard particle portions) are bonded to each other via the interface therebetween.
[0105] As described above, the above-mentioned predetermined copper alloy particles in a non-molten state to prevent the precipitation of the added elements or a mixture comprising the above-mentioned predetermined copper alloy particles and hard particles are blown onto a substrate to form a coating layer having the above-mentioned predetermined copper alloy portion, or the above-mentioned predetermined copper alloy portion and the hard particle portion, wherein these portions (for example, between the copper alloy portion, between the copper alloy portion and the hard particle portion, and between the hard particle portion) are bonded to each other via the interface therebetween. Thus, a coating layer having excellent wear resistance can be effectively formed. In other words, by forming a coating layer by means of a method such as dynamic spraying, cold spraying or warm spraying, a coating layer having excellent wear resistance can be effectively formed. However, the sliding member of the present invention is not limited to those manufactured by this method.
[0106] A more specific manufacturing method will be described further in detail.
[0107] As described above, when blowing the copper alloy particles or mixture onto the substrate, it is preferred that the copper alloy particles or mixture be blown onto the substrate at a speed such that a plastically deformed portion is formed on at least one of the substrate and the coating layer when the copper alloy particles are blown onto the substrate. This allows for efficient formation of a coating layer with further improved wear resistance.
[0108] However, the blowing speed of the copper alloy particles is not limited to the above speeds. For example, the particle speed range is preferably 300 m / s to 1200 m / s, more preferably 500 m / s to 1000 m / s, and still more preferably 600 m / s to 800 m / s. The pressure range of the working gas supplied for blowing the particles is preferably 2 MPa to 5 MPa, more preferably 3.5 MPa to 5 MPa. When the pressure of the working gas is less than 2 MPa, sufficient particle speed cannot be achieved, which results in a large porosity. However, it goes without saying that these are not limited to the above ranges and can be outside these ranges as long as the effects of the present invention can be demonstrated.
[0109] The working gas temperature is not particularly limited. However, for example, it is preferably in the range of 400°C to 800°C, more preferably 600°C to 800°C. When the working gas temperature is less than 400°C, wear resistance may be reduced due to the large porosity. When the working gas temperature exceeds 800°C, the nozzle may clog. However, it goes without saying that the temperature is not limited to these ranges and may be outside these ranges as long as the effects of the present invention are exhibited.
[0110] The type of working gas is not particularly limited. However, examples of working gases include nitrogen and helium. One working gas may be used alone, or more than one working gas may be used in combination. In addition, a mixture of fuel gas and nitrogen may also be used.
[0111] After forming the coating layer, the sliding component can be aged or tempered at 250°C to 500°C for, for example, 0.5 to 4 hours. This can improve wear resistance. For example, this aging or tempering can also be performed during a test run during an inspection after engine assembly, utilizing heat from the combustion chamber.
[0112] In addition, the copper alloy particles used as the material are not particularly limited. However, it is preferred to use those in a non-molten state and made of the above-mentioned predetermined copper alloy particles. Needless to say, the copper alloy before precipitation hardening is preferred. For example, the copper alloy particles are preferably in a supersaturated solid solution state. Since the copper alloy particles in the supersaturated solid solution state show high ductility, in other words, high deformability, the coating layer can be effectively formed and the film forming property can be improved. The particles in the supersaturated solid solution state are not particularly limited. For example, it is preferred to use fast-solidifying particles obtained by fast solidification using atomization (atomization). When the copper alloy particles collide with a substrate, etc., a fine hard phase (precipitation phase) is formed due to the pressure generated by the impact and the frictional heat generated by the difference in deformation speed between the particles and the substrate when the particles are flattened. As a result, the strength of the coating layer increases.
[0113] The copper alloy particles used as the material are not particularly limited. However, the compressive strength of the particles is preferably 50 N / mm 2 Up to 110N / mm 2 By forming a sliding member using such copper alloy particles, a coating layer having excellent wear resistance can be efficiently formed.
[0114] In the present invention, "compressive strength of particles" is defined as the compressive strength when a load is applied to the particles using a flat indenter or the like, and the particle size in the direction of the load application changes by 10%. The measurement method conforms to JIS R 1639-5 "Test methods for properties of fine ceramic particles - Part 5: Compressive strength of single particles", and the test load is 500 mN.
[0115] The hard particles used as the material are not particularly limited. However, they are preferably in a non-molten state, are preferably harder than copper alloy particles, and preferably have a non-spherical shape. For example, alloy particles are preferably used, or a mixture thereof is preferably used in any proportion. As alloy particles, iron alloy particles, cobalt alloy particles, chromium alloy particles, nickel alloy particles, or molybdenum alloy particles are preferably used, or a mixture thereof is preferably used in any proportion.
[0116] The hard particles used as the material are not particularly limited. However, particles produced by water atomization are preferably used. When producing particles by water atomization, the droplets are deformed by the impact of water on the electron droplets; at this point, the droplets are cooled by the water and retain their deformed shape, resulting in a non-spherical shape. On the other hand, with the gas blowing technique, cooling will be insufficient, and the particles will return to their spherical shape.
[0117] The grain size of the copper alloy particles and hard particles used as materials is not particularly limited. However, the particle size is preferably less than 150 μm, and more preferably less than 75 μm. The particle size of the particles can be adjusted with a sieve or by an appropriate method well known in the art. Here, as "particle size", the d95 based on quantity measured and calculated using an image analysis type particle size distribution measuring instrument can be used. The "particle size" for measuring and calculating such particle size can be, for example, the maximum distance between any two points on the contour line of the observed particle (observation surface). However, "particle size" is not limited thereto, and for example, the diameter of the equivalent circle of the observed particle (observation surface) can be used. In addition, the d95 based on quantity measured and calculated using a laser diffraction scattering type particle size distribution measuring instrument can also be used. By forming a coating layer using such copper alloy particles and hard particles, a coating layer with excellent wear resistance can be effectively formed.
[0118] The average particle size of the copper alloy particles and hard particles used as materials is not particularly limited. However, the average particle size range is, for example, preferably 5 μm to 40 μm, more preferably 20 μm to 40 μm. If the average particle size is less than 5 μm, low fluidity will result in insufficient particle supply. If the average particle size exceeds 50 μm, insufficient particle speed during film formation will result in poor film formation. As the "average particle size", for example, the average particle size (d50) based on the number can be used, wherein d50 is measured and calculated using an image analysis type particle size distribution measuring instrument. As the "particle size" for measuring and calculating the average particle size, for example, the maximum distance between any two points on the contour line of the observed particles (observation surface) can be used. However, the "particle size" is not limited to this, and for example, the diameter of the equivalent circle of the observed particles (observation surface) can be used. Alternatively, the average particle size (d50) based on the number measured and calculated using a laser diffraction scattering type particle size distribution measuring instrument can be used. However, needless to say, these are not limited to these ranges, and can be outside these ranges as long as the effect of the present invention can be shown.
[0119] Furthermore, although not particularly limited, the average particle size of the copper alloy particles is preferably smaller than that of the hard particles. By forming a sliding member using such copper alloy particles and hard particles, a coating layer having excellent wear resistance can be efficiently formed.
[0120] The aspect ratio of the copper alloy particles and hard particles used as materials, measured as a median value, is not particularly limited. As such an aspect ratio, an aspect ratio measured and calculated using an image analysis particle size distribution measuring instrument can be used. Of course, the aspect ratio can be measured and calculated using a scale by magnifying a scanning electron microscope (SEM) image of each particle.
[0121] Example
[0122] The present invention will be described in more detail below by way of examples. However, the present invention is not limited to these examples.
[0123] Example 1
[0124] First, copper-nickel-silicon alloy powder (composition: Cu-3Ni-0.7Si, water atomized particles, particle size (d95): 60.7 μm, average particle size (d50): 27.7 μm, aspect ratio (median): 1.59, compressive strength: 67.1 N / mm) was prepared. 2 , Vickers hardness: 64.1HV0.01) as the copper alloy particles used as the raw material.
[0125] Particle size (d95) is based on quantity and is measured and calculated with an image analysis type particle size distribution measuring instrument. As "particle size", the maximum distance between any two points on the outline of the observed particles (observation surface) is adopted. Average particle size (d50) is based on quantity and is measured and calculated with an image analysis type particle size distribution measuring instrument. As "particle size", the maximum distance between any two points on the outline of the observed particles (observation surface) is adopted. In addition, for aspect ratio (median value), the scanning electron microscope (SEM) image is magnified and measured and calculated with a scale. In addition, for compressive strength, a micro compression tester (MCT-510) manufactured by Shimadzu Corporation is used to apply a load to the particles, and the compressive strength is measured when the particle size changes by 10% along the direction of the load. In order to calculate the arithmetic mean, 10 are measured. In addition, Vickers hardness is measured and calculated according to the Vickers hardness test defined in Japanese Industrial Standard (JIS Z 2244). In order to calculate the arithmetic mean, 10 are measured.
[0126] Meanwhile, assuming that the target coating layer thickness was 0.2 mm in a state where processing of a seat portion of an engine valve for a cylinder head was completed, a pre-processed aluminum base material (Japanese Industrial Standard H 4040A5056) was prepared.
[0127] Then, the prepared aluminum substrate was mounted on a turntable, and while the turntable was rotating, the prepared copper alloy particles were blown onto the prepared aluminum substrate using a high-pressure cold spray device (PCS-1000, manufactured by Plasma Giken Co., Ltd., working gas type: nitrogen, temperature: 600°C, particle speed: 700 m / s to 750 m / s, pressure: 4 MPa) to form a coating layer with a thickness of 0.4 mm to 0.5 mm on the substrate.
[0128] After that, the sliding member of this embodiment is obtained by machining into the shape of the seat portion of the engine valve of the actual cylinder head. The thickness of the coating layer is 0.2 mm (the same applies hereinafter).
[0129] Examples 2 to 4
[0130] As shown in Table 1, sliding members of each example were obtained by repeating the same operation as in Example 1 except that the specifications and mixing ratios of the copper alloy particles and the hard particles were changed. "Co-Mo-Cr" in Table 1 indicates a cobalt-based alloy.
[0131] Comparative Examples 1 to 3
[0132] As shown in Table 2, sliding members of respective examples were obtained by repeating the same operations as in Example 1 except that the specifications of the copper alloy particles were changed.
[0133]
[0134]
[0135] The Vickers hardness of the copper alloy portion and the hard particle portion in the coating layer of each embodiment in Tables 1 and 2 was measured and calculated according to the Vickers hardness test defined in Japanese Industrial Standard (JIS Z 2244). In order to calculate the arithmetic mean, measurement was performed at 10 locations. In addition, the results of the observation of scanning electron microscope (SEM) images and transmission electron microscope (TEM) images and energy dispersive X-ray (EDX) spectral analysis were used to determine the measurement position. In addition, the ratio and porosity of the hard particle portion in the cross section of the coating layer of each embodiment were calculated by observing the scanning electron microscope (SEM) images of the cross section of the coating layer for multiple times and image processing such as binarization of the scanning electron microscope (SEM) cross-sectional image. The precipitated phase of the copper alloy portion of each embodiment was determined by observing the transmission electron microscope (TEM) images of the cross section of the coating layer and energy dispersive X-ray (EDX) analysis. The presence or absence of the intermediate layer in the cross section of the sliding member of each embodiment and the presence or absence of the plastic deformation portion were determined by observing the scanning electron microscope (SEM) images of the cross section of the coating layer and energy dispersive X-ray (EDX) analysis. In each of Examples 1 to 4, the precipitated phase was observed, and the plastically deformed portion in the base material and the coating layer was observed.
[0136] Performance evaluation
[0137] The sliding members of the above-described respective examples were evaluated for the following properties.
[0138] Wear resistance
[0139] Figure 13 This is a cross-sectional view showing the outline of the wear test device. Figure 13 As shown in FIG, a wear test device similar to an engine valve actuation mechanism is constructed from actual engine components, such as a valve spring 42, an engine valve 43, a valve stem seal 44, a valve guide 45, a cylinder head 46, 46', and a pin 49. The sliding members (1, 2, 3, 4) of the aforementioned embodiments serve as the seat 46A of the engine valve 43 in the cylinder head 46. The sliding members (1, 2, 3, 4) include a predetermined coating layer 20 formed on a substrate 10. In the figure, the engine valve 43 is shown in an open state. The engine valve 43 is reciprocated in the vertical direction indicated by arrow Y in the figure by an eccentric cam (not shown), causing the engine valve 43 to repeatedly open and close. The sliding surface 46a of the seat 46A of the engine valve 43 in the cylinder head 46 is exposed to a high temperature environment by the flame F of a gas burner B. The temperature of the seat 46A is measured using a thermometer T. Cooling water W circulates within the cylinder head 46.
[0140] The wear amount was measured and calculated using the aforementioned wear tester under the following test conditions. Specifically, the shape of the seat portion of an engine valve used in a cylinder head was measured using a shape measuring instrument before and after the test. The wear amount was measured at four points, and the average value was calculated to serve as the wear amount. The results are shown in Tables 1 and 2.
[0141] Test conditions
[0142] - Temperature: 300°C (assuming the seat of the engine valve of the cylinder head on the exhaust port side);
[0143] -Number of inputs: 540,000
[0144] As seen from Tables 1 and 2, Examples 1 to 4 within the scope of the present invention showed less wear than Comparative Examples 1 to 3 outside the scope of the present invention, and had excellent wear resistance even at high temperatures.
[0145] Examples 1 to 4 also use copper alloy particles and therefore have excellent thermal conductivity.
[0146] It is believed that the sliding components with excellent wear resistance of Examples 1 to 4 are obtained by forming the following coating layer on the substrate, wherein the coating layer includes the above-mentioned predetermined copper alloy portion, preferably the above-mentioned predetermined copper alloy portion and the hard particle portion, wherein these portions (for example, between the copper alloy portions, between the copper alloy portion and the hard particle portion, and between the hard particle portions) are bonded to each other via the interface between them.
[0147] Furthermore, it is considered that the sliding members having excellent wear resistance of Examples 1 to 4 were obtained because at least one copper alloy portion had at least one precipitated phase including nickel silicide in the interior and / or interface of the copper alloy portion.
[0148] Furthermore, it is considered that the sliding members having excellent wear resistance in Examples 1 to 4 were obtained because at least one of the base material and the coating layer had a plastically deformed portion.
[0149] Furthermore, it is considered that since the porosity in the cross section of the coating layer is 1 area % or less, the sliding members having excellent wear resistance in Examples 1 to 4 are obtained.
[0150] Figure 14 This is a transmission electron microscope (TEM) cross-sectional image of the vicinity of the interface between the substrate 10 and the coating layer 20 of the sliding member of Example 3. Figure 15 To illustrate the sliding member of embodiment 3 Figure 14 Graph showing the results of energy dispersive X-ray (EDX) analysis (linear analysis) of line Z in FIG. Figure 14 Point P and Figure 15 Point P in represents the same position. Figure 15The position of 0.0 μm corresponds to Figure 14 The position of 2.0 μm corresponds to the end of the line Z on the substrate 20 side, and the position of 2.0 μm corresponds to the end of the line Z on the coating layer 20 side.
[0151] like Figure 14 and 15 As shown, the sliding member includes an aluminum alloy substrate 10 and a copper alloy coating layer 20 formed on the substrate 10, with an intermediate layer formed between the substrate 10 and the coating layer 20. The intermediate layer is formed at a position of approximately 0.75 μm to 1.31 μm. In addition, a diffusion layer is formed at a position of approximately 0.75 μm to 0.96 μm and at a position of approximately 1.23 μm to 1.31 μm. The diffusion layer also has a gradient structure in composition. At a position of approximately 0.96 μm to 1.23 μm, the ratio of aluminum, magnesium, and copper is approximately Al:Mg:Cu = 2:1:1 (atomic ratio), indicating the formation of an intermetallic compound layer.
[0152] In this manner, it is also believed that because the sliding member includes an intermediate layer including both a diffusion layer and an intermetallic compound layer formed in at least a portion of the gap between the base material and the coating layer, the sliding member having excellent wear resistance of Example 3 is obtained. Furthermore, it is also believed that because an intermediate layer including a diffusion layer having a gradient structure in its composition is provided, or because an intermediate layer having a structure in which an intermetallic compound layer is provided between diffusion layers having a gradient structure in its composition is provided, the sliding member having high wear resistance of Example 3 is obtained.
[0153] Furthermore, it is also considered that since the hard particle portion is derived from hard particles such as cobalt-based alloy particles, the sliding members having excellent wear resistance of Examples 1 to 4 are obtained.
[0154] Furthermore, it is also considered that because the method for manufacturing the sliding member has a step of blowing a mixture containing the above-mentioned predetermined copper alloy particles in a non-molten state, preferably a mixture containing the above-mentioned predetermined copper alloy particles in a non-molten state and hard particles, onto a substrate to form a coating layer on the substrate, the sliding members having excellent wear resistance of Examples 1 to 4 are obtained.
[0155] Furthermore, it is also considered that the sliding members having excellent wear resistance of Examples 1 to 4 are obtained because, when the above-mentioned predetermined copper alloy particles or mixture are blown onto the substrate, the copper alloy particles or mixture are blown onto the substrate at a speed at which a plastic deformation portion is formed on at least one of the substrate and the coating layer when the copper alloy particles are blown onto the substrate.
[0156] Furthermore, it is also considered that the sliding members having excellent wear resistance of Examples 1 to 4 were obtained because the copper alloy particles were prepared by water atomization, because the copper alloy particles were in a supersaturated solid solution state, or because the copper alloy particles were rapidly solidified particles.
[0157] In addition, it is also considered that the compressive strength of the copper alloy particles is 50N / mm 2 Up to 110N / mm 2 , thus obtaining the sliding members of Examples 1 to 4 having excellent wear resistance.
[0158] Furthermore, it is also considered that since the particle sizes of the copper alloy particles and the hard particles are 75 μm or less, the sliding members having excellent wear resistance of Examples 1 to 4 are obtained.
[0159] Furthermore, it is also considered that the sliding member having excellent wear resistance of Example 3 was obtained because the average particle size of the copper alloy particles was smaller than the average particle size of the hard particles.
[0160] Although the present invention has been described by way of some embodiments and examples, the present invention is not limited thereto, and various changes can be made within the scope of the present invention.
[0161] For example, the components described in the above embodiments and examples are not limited to the respective embodiments and examples. For example, structural features such as the specifications and mixing ratio of the copper alloy particles and hard particles, as well as film forming conditions, may be varied. Furthermore, structural features of each embodiment or example may be combined differently from the combinations described in the above embodiments and examples.
[0162] Description of Reference Numerals
[0163] 1,2,3,4: Sliding components
[0164] 10: Base material
[0165] 10b: Plastic deformation part
[0166] 20: coating layer
[0167] 20a: Porosity
[0168] 20b: Plastic deformation part
[0169] 21: Copper Alloy Department
[0170] 21a: Interface
[0171] 23: Hard particle part
[0172] 25: Precipitated phase
[0173] 30: Middle layer
[0174] 40: Cam lobe
[0175] 41: Valve tappet
[0176] 42: Valve spring
[0177] 43: Engine valve
[0178] 43A: Valve stem
[0179] 43a: Sliding surface
[0180] 43B: Valve face
[0181] 43b: Sliding surface
[0182] 44: Valve stem seal
[0183] 45: Valve guide
[0184] 45a: Sliding surface
[0185] 46,46': Cylinder head
[0186] 46A: Seat
[0187] 46a: Sliding surface
[0188] 47: Exhaust port
[0189] 48: Retaining parts
[0190] 49: Production and Sales
[0191] 60: Connecting rod
[0192] 60A: Large end
[0193] 61: Crank pin
[0194] 62: Bearing Metal
[0195] 62a: Sliding surface
[0196] B: Gas burner
[0197] F: Flame
[0198] T: Thermometer
[0199] W: cooling water
Claims
1. A sliding member comprising: substrate; and A coating layer formed on the substrate; wherein the coating layer includes a copper alloy portion derived from a plurality of precipitation-hardened copper alloy particles, and an alloy particle portion that is harder than the copper alloy portion and derived from a plurality of alloy particles, the copper alloy portions being bonded to each other and to the alloy particle portion via interfaces therebetween, The copper alloy portion contains nickel and silicon as additive elements, and The copper alloy portion contains 3 to 5 mass % of nickel, The copper alloy particles are in a supersaturated solid solution state, The sliding member is manufactured by the following manufacturing method: The manufacturing method comprises the steps of blowing a non-molten powder of the precipitation-hardening copper alloy or a non-molten mixed powder comprising the powder and a harder powder than the powder onto the substrate to form the coating layer on the substrate. The powder is in a supersaturated solid solution state. 2 . The sliding member according to claim 1 , wherein a precipitated phase is contained at an interface between the copper alloy portion and the alloy grain portion. 3 . The sliding member according to claim 2 , wherein the precipitated phase is composed of Ni 2 Si. The sliding member according to claim 1 , further comprising a diffusion layer at an interface between the copper alloy portion and the alloy particle portion. 5 . The sliding member according to claim 1 , wherein the alloy particle portion includes at least one alloy particle selected from the group consisting of iron-based alloy particles, cobalt-based alloy particles, chromium-based alloy particles, nickel-based alloy particles, and molybdenum-based alloy particles. 6 . The sliding member according to claim 1 , wherein at least one of the copper alloy portions includes at least one precipitation phase containing nickel silicide in an interior and / or an interface of the copper alloy portion. 7 . The sliding member according to claim 1 , wherein at least one of the base material and the coating layer includes at least one plastically deformed portion. 8 . The sliding member according to claim 1 , wherein a porosity in a cross section of the coating layer is 3 area % or less. 9 . The sliding member according to claim 1 , comprising at least one intermediate layer including at least one of a diffusion layer and an intermetallic compound layer, the at least one intermediate layer being formed in at least a portion of a gap between the base material and the coating layer. 10 . The sliding member according to claim 1 , wherein the average particle size of the copper alloy particles is smaller than the average particle size of the hard particles.
11. A sliding member for an internal combustion engine, comprising the sliding member according to any one of claims 1 to 10 at a sliding portion of the internal combustion engine.
Citation Information
Patent Citations
Panel connection device for construction
JP1977002024A
Cold spray of nickel-base alloys
CN103160769A
Coating-coated sliding member
JP5175449B2